Who Counts as Trans? A Critical Discourse Analysis of Trans Tumblr Posts. (January 2022) - Jacobsen, Kai; Devor, Aaron; Hodge, Edwin
Internet and social media sites have long served as a rich form of community-building and knowledge exchange within transgender communities. In particular, Tumblr has become a popular site among trans youth in recent years. Paralleling changes in medical and mainstream societal understandings of what it means to be transgender, trans Tumblr users have engaged in dialogue and debate about the definitions and limits of trans identity. While research has established the potential for positive identity-formation among LGBTQ+ youth on Tumblr, it is also important to consider how online trans communities may re-inscribe hegemonic narratives in addition to disrupting dominant discourses and ideologies. Using a critical discourse analysis of Tumblr posts, this research analyses how trans Tumblr users define "who counts as trans, " including how users define gender dysphoria and its relationship to trans identities. Our findings provide critical insight into how trans communities define the boundaries of their identities in a struggle for visibility, resources, and respect.